# Solve for W 5/6*(Wn)=60 56⋅(Wn)=60
Multiply both sides of the equation by 65.
65⋅56⋅(Wn)=65⋅60
Simplify both sides of the equation.
Simplify 65⋅56⋅(Wn).
Cancel the common factor of 6.
Cancel the common factor.
65⋅56⋅(Wn)=65⋅60
Rewrite the expression.
15⋅5⋅(Wn)=65⋅60
15⋅5⋅(Wn)=65⋅60
Cancel the common factor of 5.
Cancel the common factor.
15⋅5⋅(Wn)=65⋅60
Rewrite the expression.
1⋅(Wn)=65⋅60
1⋅(Wn)=65⋅60
Multiply Wn by 1.
Wn=65⋅60
Wn=65⋅60
Simplify 65⋅60.
Cancel the common factor of 5.
Factor 5 out of 60.
Wn=65⋅(5(12))
Cancel the common factor.
Wn=65⋅(5⋅12)
Rewrite the expression.
Wn=6⋅12
Wn=6⋅12
Multiply 6 by 12.
Wn=72
Wn=72
Wn=72
Divide each term by n and simplify.
Divide each term in Wn=72 by n.
Wnn=72n
Cancel the common factor of n.
Cancel the common factor.
Wnn=72n
Divide W by 1.
W=72n
W=72n
W=72n
Solve for W 5/6*(Wn)=60

## Our Professionals ### Robert Kristofer ### Anna Frok ### Magnus Flores ### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top